Comparative Views of Health Professionals and Traditional Healers on the trado-medical uses of Impepho leaf (Helichrysum odoratissimum) from Eastern Cape and Kwazulu-Natal provinces in South Africa - Belani, Aviwe; Oladimeji, Kelechi Elizabeth; Hyera, Francis Leonard (Journal of Ecohumanism, 2025)
Background: Impepho (Helichrysum odoratissimum) is a plant utilised for spiritual and traditional medicinal purposes within South African culture. However, there are little or no empirical evidence on the trado-medical use of Impepho hence , this study aimed to close this gap by exploring differing views on trado-medical uses of impepho as a potential resource for drug development advancement. Methods: The study design involved the use of a qualitative research approach where ten (10) key in-depth interviews (KIIs) were conducted. The study population that was purposively sampled included six (6) traditional healers and four (4) health professionals across three (3) districts each in Eastern Cape and Kwa-Zulu Natal provinces, South Africa. The KIIs were conducted using a question guide in the participants’ preferred languages, which were audio recorded, transcribed verbatim, and translated for thematic analysis. Results: The mean/median age of the traditional healers and health professionals was 53 years. Average duration for both categories of participants in the traditional and medical professionals was 21 years. The emerged themes included Impepho significance and uses, Impepho in modern medicine, potential use, and integration into modern medicine. All participants recognised the cultural and medicinal importance of Impepho. Crucial aspects reflecting key views by each participant category were that the traditional practitioners referred to Impepho as a spiritual intercessory for communicating with the spirits and healing (communication with ancestors). In contrast, modern professionals viewed it as potential for drug discovery due to both the therapeutic and spiritual functions, they affirmed that the leaf has trado-medical and healing uses. Participants emphasised that there needs to be respect for cultural practices when considering Impepho for further drug discovery empirical research study (Impepho in modern medicine and cultural and healing uses of Impepho). Conclusions: The study highlights the importance of Impepho in traditional healers and health professionals, urging further research to confirm its medicinal value and determine the appropriate dose. Successful formulations require a collaborative approach, ensuring authenticity and effective treatment without harm to humans. Further research is needed to enhance healthcare delivery and policies.